Fine mapping of the major-effect QTL qPHS4.1 revealed a CsDOG1 gene controlling pre-harvest sprouting in cucumber (Cucumis sativus L.) - Cao, Mingming; Deng, Qiang; Wang, Huizhe; Liu, Changyue; Zhao, Haiyan; Yang, Ruihuan (Frontiers in Plant Science, 2025)
Pre-harvest sprouting (PHS) in cucumber (Cucumis sativus L.) significantly reduces seed quality and yields in seed industry. The identification of PHS-associated quantitative trait loci (QTL) provides valuable genetic insights for improving PHS resistance in cucumber breeding practices. In this study, near-isogenic lines (NILs) targeting the major effect QTL locus were developed by the backcrossing of the highly PHS-sensitive donor parent P60 with the PHS-resistant recurrent parent Q12. PHS phenotypes of qPHS4.1Q12 and qPHS4.1P60 were consistent with the respective Q12 and P60, confirming that the qPHS4.1 locus has a major-effect on PHS in cucumber. Using BC4F2 and BC4F3 populations, the qPHS4.1 was fine-mapped to a 69.34 kb region, explaining 38.8% phenotypic variation. Through map-based cloning, CsaV3_4G032930 (designated CsDOG1) was identified as the candidate gene, which encodes a DOG1 (Delay of Germination 1) domain-containing protein. Sequence analysis revealed that the mutation in P60 was a 3-bp deletion in the second exon of this gene (designated Csdog1), leading to a single amino acid deletion. Expression profiling revealed that CsDOG1 exhibits strict seed-specific expression, with minimal transcripts in vegetative tissues. Promoter analysis demonstrated identical promoter sequence between Q12 and P60. The cis-acting regulatory elements, including several tissue-specific expression motifs, ABREs for ABA responsiveness and transcriptional promoter or enhancer elements were identified. Subcellular localization analysis revealed that the CsDOG1 protein was mainly localized in nucleus. Knockout of CsDOG1 gene in the Q12 background resulted in mutants exhibiting extreme PHS susceptibility, confirming that CsDOG1 is the causal gene responsible for PHS resistance underlying qPHS4.1 locus. This study establishes a crucial theoretical foundation for elucidating the genetic mechanisms controlling PHS and offers valuable genetic resources for cucumber PHS-resistance breeding.